THE EFFECT OF THE TGT MODEL ASSISTED BY THE ‘PLAY WITH DYNO’ SNAKES AND LADDERS MEDIA ON FIRST GRADE STUDENT’S MATHEMATICS LEARNING OUTCOMES - Putra, Fahrizal Ananda; Setyawan, Agung (Universitas Trunojoyo Madura, 2025)
This study aims to determine the effect of the cooperative learning model of the Teams Games Tournament (TGT) type assisted by the snakes and ladders media